Teaching at university : - Morss, Kate (SAGE Publications, 2005)
Teaching at University has been written to provide you with the basic skills required to enter those first lectures, tutorials, lab-sessions, and assessments with confidence. Clear and engaging throughout, this guide will offer: Accessible and generic language to support postgraduates in all disciplines, Basic but relevant advice, A direct and practical approach and style, An emphasis on helping you to get started and build up your confidence in the first few classes you teach, and Integration of theory (in small doses) with practice.